RHOA controls oncogenic B cell receptor signaling in aggressive lymphoma - Ariana N. Jacobs; Dominique Jahn; Tim Beringer; Sebastian Wolf; Ramesh K. Krishnan; Michael Engelke; Björn Häupl; Silvia Münch; Niklas Dienstbier; Martine Pape; Marion Bodach; Xin Yu; et al. (Proceedings of the National Academy of Sciences, 2026)
Diffuse large B cell lymphoma (DLBCL) is characterized by a variety of specific genetic alterations that impact signaling pathway dependencies and therapeutic outcomes. Among the recurrently mutated genes, we identified RHOA , a member of the small GTPase family, as a selective dependency in DLBCL. Here, we show that RHOA function is essential for the survival of ABC DLBCL cells because it sustains oncogenic B cell receptor (BCR) signaling through maintaining a signaling-permissive conformation of the cortical actin network. This enables the formation of active BCR microclusters at the cell surface, ultimately resulting in constitutive, BCR-driven NF-κB survival signaling. Moreover, we found that RHOA controlled endocytosis of the BCR and thereby the assembly of the endolysosomal My–T–BCR multiprotein complex, a central activator of NF-κB consisting of MYD88, Toll-like receptor 9, and the internalized BCR. The recurrent DLBCL-associated RHOA R5W mutation rendered RHOA constitutively active in its GTP-bound state and changed the conformation of the actin network from primarily filamentous actin to globular actin. This altered actin state led to an increase in BCR microcluster formation, amplification of NF-κB signaling, and resistance to inhibitors targeting chronic active BCR signaling. Hence, our study establishes RHOA and its mutant isoforms as critical regulators of oncogenic BCR signaling in DLBCL.